Hugo Kārļa Grotusa glezna “Viktorijas ūdensroze” - Jamonte, Daiga (My University, 2020)
LU Muzeja Botānikas un mikoloģijas kolekcijās glabājas latviešu botāniķim profesoram Paulam Galeniekam (1891 - 1962) piederējusī latviešu mākslinieka Hugo Grotusa glezna (1884 - 1951) ar attēlotu viktorijas ūdensrozi. Raksts veltīts šim artefaktam.

The Botanical and Mycological Collections of the Museum of the University of Latvia contain a painting by the Latvian artist Hugo Grotus (1884 - 1951), owned by the Latvian botanist Professor Paul Galeniek (1891 - 1962), depicting a victoria waterlilie. The article is dedicated to this artifact.
Hugo Karl Grotus' painting "Victoria waterlilie"
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects; botany; Victoria; Pauls Galenieks; Hugo Grotuss; LU Botānikas katedra; Latvian painting; glezniecība